Food and agriculture in Ethiopia: Progress and policy challenges - Dorosh, Paul A.; Rashid, Shahidur (University of Pennsylvania Press, 2012)
The perception of Ethiopia projected in the media is often one of chronic poverty and hunger, but this bleak assessment does not accurately reflect most of the country today. Ethiopia encompasses a wide variety of agroecologies and peoples. Its agriculture sector, economy, and food security status are equally complex. In fact, since 2001 the per capita income in certain rural areas has risen by more than 50 percent, and crop yields and availability have also increased. Higher investments in roads and mobile phone technology have led to improved infrastructure and thereby greater access to markets, commodities, services, and information. In Food and Agriculture in Ethiopia: Progress and Policy Challenges, Paul Dorosh and Shahidur Rashid, along with other experts, tell the story of Ethiopia's political, economic, and agricultural transformation. The book is designed to provide empirical evidence to shed light on the complexities of agricultural and food policy in today's Ethiopia, highlight major policies and interventions of the past decade, and provide insights into building resilience to natural disasters and food crises. It examines the key issues, constraints, and opportunities that are likely to shape a food-secure future in Ethiopia, focusing on land quality, crop production, adoption of high-quality seed and fertilizer, and household income.